Countering COVID-19: Cases in Crisis Response - de Jesus, Edilberto (Archīum Ateneo, 2021)
The enormity of the COVID-19 pandemic urgently calls for a proactive and strategic response from across all sectors at all levels: global, national, and local. Countering COVID-19: Cases in Crisis Response, with its wide range of essays, makes the case for a coordinated and truly whole-of-society approach to contain, adapt to, and overcome the pandemic while laying bare preexisting systemic and structural inequalities. There is no other more critical time to confront these than now. "Part-chronicle of an ongoing crisis and part-resource for policy analysis, the scope of this ad interim work is as vast as the national experience: from rural locales in BARMM and urban poor communities in Metro Manila to OFWs across the globe. As the pandemic has made clear, the “medical” is inseparable from the “cultural,” the “social,” the “environmental,” and the “political,” and the case studies in this book illuminate these intersections in ways that inform and challenge scholars, policy makers, and the public." —Gideon Lasco, author, The Philippines Is Not a Small Country